ANASIR BABAD DESA SIRKANDI DALAM PERSFEKTIF STRUKTURALISME LEVI-STRAUSS - Ery Agus Kurnianto (tuahtalino, 2021)
The Babad Desa Sirkandi is one of the folklore that lives and develops in the social community of the Banjarnegara community. Babad Desa Sirkandi is an interesting topic of this study  because as far as the author's knowledge there has been no research that examines the chronicle (Babad). Babad Desa Sirkandi is a baboon of folklore in the village of Sirkandi. To analyze the chronicle, researcher used descriptive methods. The approach used to analyze the Babad Sirkandi is an objective approach. This approach was carried out to analyze the intrinsic elements that built the Babad Desa Sirkandi story. the object this research is folklore from Banjarnegara in the form of babad, namely Babad Desa Sirkandi. Based on the  research result, it can be concluded that (1) Babad Desa Sirkandi consists of eight episodes.; (2) the babad is formed by 56 mythems: (3) the identified myths have five binary opposition structures; (4) Babad Desa Sirkandi has three historical life structures: (5) Babad Desa Sirkandi has three layers of social strata, namely the upper layer, middle layer, and lower layer; (6) Karanggintung Village community believes  in the concept of Manunggaling Kawula Gusti: (7) there are three symbolic messages.